PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN PERTUMBUHAN PENJUALAN TERHADAP PENGUNGKAPAN ICSR LEMBAGA KEUANGAN SYARIAH DI INDONESIA - Agung Hendratmoko; Dul Muid (Diponegoro Journal of Accounting, 2017)
This study aims to determine the effect of profitability, firm size, and sales growth of ICSR disclosure of Islamic financial institutions in Indonesia.The population used in this study is all sharia financial institutions go public listed on the Indonesia Stock Exchange 2010-2015. The sample technique used in this study is the selection of samples with judgment / purposive sampling. The analysis tool used is multiple linear regression analysis.Based on the results of the tests conducted can be concluded that: 1) Return on Assets (ROA) proved to significantly affect the Islamic Corporate Social Responsibility (ICSR), this is evidenced by the value of t count of 4.170 and significance of 0.000. 2) The size of the company proved to significantly affect the Islamic Corporate Social Responsibility (ICSR), this is evidenced by the value of t count of 3.426 and significance of 0.000. 3) Sales growth proved to significantly affect the Islamic Corporate Social Responsibility (ICSR), this is evidenced by the magnitude of t count value of 2.402 and significance of 0.008.